Implementing Information and Communication Technologies in Educating Knowledge Workers - Vranes, Aleksandra; Markovic, Ljiljana (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
The possession and access to relevant information, as well as to the newly created knowledge, became the main asset within knowledge-based economies, and, hence, societies. In order to achieve considerable level of innovation and competitiveness in the modern labor market, companies are striving to manage knowledge they dispose with in the most optimal way. One of the basic preconditions for accomplishing this goal is to employ highly skilled knowledge workers. Given that this is the workforce of the future, all levels of education, particularly institutions at the university level, must adapt their curricula in order to form professionals capable of anticipating and solving problems within the business environment. Considering that these professionals must remain experts in their scientific fields during their entire career, the concept of lifelong learning especially applies to them. Hence, universities must pay particular attention not only to educating future knowledge workers, but also to providing constant additional training, primarily through digital means and distance type of learning.  Knowledge workers are encouraged to use digital tools and methods as much as possible for the purpose of their professional development. In order to achieve and maintain a high level of competitiveness in the ever-changing labor market, these experts are also required to stay constantly and adequately informed, which they mostly accomplish by means of digital media. Therefore, it became obvious that when educating future knowledge workers universities have to implement ICT to a much greater extent. Digital tools should also be utilized at the university level in order to incite a higher level of creativity of university students, as this is one of the essential features of knowledge professionals. Encouraging inventiveness at the university level is particularly important so that future knowledge workers can acquire the habit of transferring theoretical knowledge in an original manner into new applicable knowledge. Within this paper, we will offer a review of current knowledge workers‟ education at the university level and possible innovations in this regard, particularly with the application of digital tools in lifelong education and training of future workforce based on knowledge.